Analysis of Thermo-Elastic Fracture Problem during Aluminium Alloy MIG Welding Using the Extended Finite Element Method - Kuanfang He; Qing Yang; Dongming Xiao; Xuejun Li (Applied Sciences, 2017)
The thermo-elastic fracture problem and equations are established for aluminium alloy Metal Inert Gas (MIG) welding, which include a moving heat source and a thermoelasticity equation with the initial and boundary conditions for a plate structure with a crack. The extended finite element method (XFEM) is implemented to solve the thermo-elastic fracture problem of a plate structure with a crack under the effect of a moving heat source. The combination of the experimental measurement and simulation of the welding temperature field is done to verify the model and solution method. The numerical cases of the thermomechanical parameters and stress intensity factors (SIFs) of the plate structure in the welding heating and cooling processes are investigated. The research results provide reference data and an approach for the analysis of the thermomechanical characteristics of the welding process.